Immigrant performance and selective immigration policy: a European perspective - Amelie F. Constant; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2005)
The European Union aims at a stronger participation by its population in work to foster growth and welfare. There are concerns about the attachment of immigrants to the labour force, and discussions about the necessary policy responses. Integrated labour and migration policies are needed. The employment chances of the low-skilled are limited. Whereas Europe could benefit from a substantive immigration policy that imposes selection criteria that are more in line with economic needs, the substantial immigration into the European Union follows largely non-economic motives. This paper discusses the economic rationale of a selective immigration policy and provides empirical evidence about the adverse effects of current selection mechanisms.
Keywords: F22; J15; J31; J61; J68; J82; 330; migration policy; ethnicity; migrant workers; asylum seekers; family reunification